2004
DOI: 10.1093/annonc/mdh171
|View full text |Cite
|
Sign up to set email alerts
|

Survival in nephroblastoma treated according to the trial and study SIOP-9/GPOH with respect to relapse and morbidity

Abstract: Initial therapy should be more individualized, taking the above risk groups (age in non-anaplastic WTs, poor response, anaplasia, etc.) into account, as morbidity even after relapse therapy with ifosfamide, carboplatin and etoposide was not high. Milder therapy in low stages of differentiated and of well responding WTs should be tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
67
1
9

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(87 citation statements)
references
References 37 publications
10
67
1
9
Order By: Relevance
“…Since the first SIOP protocol started in 1971, treatment intensity has been successfully reduced for the majority of patients with Wilms tumours, and survival has risen to 90% 2,[6][7][8][9][10] . Consequently, the identification of additional predictive and prognostic factors is increasingly important to improve the stratification of patients according to their individual risk.…”
Section: Treatment Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first SIOP protocol started in 1971, treatment intensity has been successfully reduced for the majority of patients with Wilms tumours, and survival has risen to 90% 2,[6][7][8][9][10] . Consequently, the identification of additional predictive and prognostic factors is increasingly important to improve the stratification of patients according to their individual risk.…”
Section: Treatment Recommendationsmentioning
confidence: 99%
“…Similar to the SIOP−2001 protocol, the UMBRELLA protocol continues to recommend preoperative actinomycin D and vincristine for patients newly diagnosed with Wilms tumour aged ≥6 months, based on results of previous SIOP trials that showed tumour downstaging using this regimen 2,6,8,9,14,17 . This benefit was also independently observed in the randomized, controlled UKW3 trial conducted by the UK Children's Cancer and Leukaemia Group (UKCCLG, previously known as the UK Children's Cancer Study Group) 18 .…”
Section: Treatment Recommendationsmentioning
confidence: 99%
“…Advanced clinical stage at presentation, particularly metastatic disease (stage IV), is an independent risk factor for treatment failure in Wilms' tumors (33), and local tumor spread (stage III) has been associated with a greater probability of local recurrence after treatment (34). Information concerning the clinical stage was available for 43 of the sporadic Wilms' tumors in our series.…”
Section: The Number Of Chromosomes Affected By Loh In Sporadic Wilms'mentioning
confidence: 99%
“…Weirich et al demonstrated that Wilms' tumor therapy should be individualized and based on the patient's age, the presence of anaplasia and the response to initial chemotherapy [8]. That analysis included 440 patients treated in accordance with the SIOP-9 protocol.…”
Section: Discussionmentioning
confidence: 99%